2006
DOI: 10.1007/s00120-006-1039-1
|View full text |Cite
|
Sign up to set email alerts
|

Benignes Prostatasyndrom (BPS)

Abstract: Today, the surgical treatment of the benign prostatic syndrome (BPS) often follows a course of drug treatment. Besides conventional transurethral resection of the prostate (TURP), which has represented the standard therapeutic option for decades, and its in part significant modifications ("vaporizing resection"; bipolar resection), much of the interest has shifted to alternative instrumental procedures like transurethral microwave therapy (TUMT), transurethral needle ablation of the prostate (TUNA) or several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 82 publications
(1 reference statement)
0
17
0
3
Order By: Relevance
“…It is very effective in experienced hands, with good tissue ablation and long-term results [1,6]. Nevertheless, certain complications are still associated with TURP, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very effective in experienced hands, with good tissue ablation and long-term results [1,6]. Nevertheless, certain complications are still associated with TURP, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, certain complications are still associated with TURP, e.g. fluid retention in about half of patients, and that are clinically relevant in 2-12% of the patients [1,13], and a transfusion rate of 5-11% [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 More recently, Reich and colleagues published a contemporary prospective evaluation of 10 654 patients who underwent TURP statewide. 8 The mortality rate was 0.10% and the cumulative short-term morbidity rate was 11.1%; both rates continuously declined compared to a previous classical study by Mobust and colleagues of 3885 patients. 6 Complications of TURP include failure to void (4.5% to 5.8%), surgical revision (1.1% to 5.6%), urinary tract infection (3.6% to 4.2%), bleeding which requires transfusions (2.0% to 2.9%) and TUR syndrome (0.8% to 1.4%).…”
Section: The Merits Of Turpmentioning
confidence: 68%
“…5 TURP has been demonstrated to be efficient, cost-effective and, most importantly, durable with low long-term complications and re-treatment rates. [6][7][8][9] The seminal multicentre randomized trial comparing TURP with watchful waiting demonstrated a 52% reduction in treatment failure in TURP, a 1% risk of urinary incontinence similar in the watchful waiting group, and an overall decline in sexual function identical to the watchful waiting group. 7 More recently, Reich and colleagues published a contemporary prospective evaluation of 10 654 patients who underwent TURP statewide.…”
Section: The Merits Of Turpmentioning
confidence: 99%